Incidencia en la depresión en el deterioro cognitivo de una adulta mayor de 79 años de la ciudad de Babahoyo - Ramírez Bazan, Joyce Andrea (2023)
Depression is immersed in the classification of unipolar mood disorders that have repercussions on other social and personal areas of an individual, with the older adult population being the most vulnerable and likely to suffer from this disorder, hindering any type of pleasure. received from the outside, also as the approach to this symptomatology is very common within psychology; however, in this population other implications such as cognitive deterioration are affected. Cognitive impairment is those alterations in the main mental functions of an individual and it encompasses behavioral and neurological aspects, the main ones that we can mention are memory, attention, language and execution, according to the results of this case study it is shown. As the affected areas of the elderly are memory and attention, however, with constant support from caregivers, family members and children, this cognitive deterioration can be slowed down or at least it is intended that it does not affect the areas that do not are relatively affected. Depression contains a number of signs and symptoms that tend to be even more noticeable in the older adult population, impairing the ability to share moments with friends, family and those people who care about said population.